Mobility analytics: plan and improve public transportation services though a business intelligence model and dashboards - Barnabé, Fábio Ruben Ferreira (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence